Impacto de um programa de ensino para cuidadoras em creche: música como condição facilitadora de condutas humanas ao lidar com bebês. - Darezzo, Margareth (2004)
The objective of this study was to verify the extent to which musical resources could impact favorably on the behavior of adults who care for children aged 0 to 3 years in crèches or school, when they are away from their mothers. There are many opportunities to ascertain the importance for the child - whether or not he reveals signs of requiring special needs or has special needs already identified - be exposed to an appropriately stimulating environment, compatible with his particular needs and possibilities. All too often, professionals responsible for the care of children in crèches work with scant information on child development, in environments prejudicial to the vast majority of children being cared for, low wages, and possessing a rather poor level of education. Using a multiple base line, two carers in two units of a kindergarten school in a city in the interior of São Paulo were exposed to three stages of a teaching program designed to prepare them to interact with babies with the help of songs; by filming bath time situations handled by these carers, it was possible to evaluate the impact of each one of the stages of intervention on aspects of the performance of these professionals, significant in the promotion of an adequate child development, in accordance with available knowledge. Information was collected relating to the performance of the carers, the data of which manifests: the low frequency of favored conduct, changes in patterns of behavior related to the signaling of manipulations and of conditions for the babies learning about their own body, with a reduction in the frequency of these behaviors as the study proceeded (low level of maintenance of these behaviors). Also observed, was an increase in the use of songs taught in the course of the program which fostered rewarding interaction between babies and the carers, relating to opportunities for the baby to develop adequately, in the case of Carer 1, and the increase in the frequency of behaviors considered, even when songs had been used, for Carer 2.